The Paris novel [large type] - Reichl, Ruth (Random House Large Print, 2024)
"When her estranged mother dies, Stella is left with an unusual inheritance: a one-way plane ticket and a note reading "Go to Paris." But Stella is hardly cut out for adventure; a childhood trauma, and her mother's negligent parenting style, have kept her strictly confined to her comfort zone, even in adulthood. When her boss encourages her to time off, Stella resigns herself to honor her mother's wishes, even if a spontaneous trip to Paris is the last thing she wants. Even in a new city, Stella can't help but fall into old habits, living cautiously and frugally. But one day, she stumbles across a consignment store and tries on a fabulous vintage dress. The shopkeeper allows her to borrow it for the day if she goes on an adventure. So Stella decides to treat herself to oysters and wine for lunch, where she has a chance encounter with a dapper octogenarian art collector, Jules. He immediately recognizes Stella needs a proper introduction to the magical side of Paris and takes her under his wing. Amid decadent meals and encounters with a veritable who's who of the 1980s Paris art and culinary worlds, Stella begins to understand what it might mean to live a bigger life. As weeks pass, Stella ends up living at the bookstore Shakespeare & Company as a "tumbleweed," uncovering a hundred-year-old art mystery, and unlocking a passion for food that may be connected to her past, and the true reason she has been sent to Paris. A feast for the senses, this novel is a testament to what it means to live deliciously: to be authentic, to embrace adventure, and to find a home in the last place you might expect"--